2019
DOI: 10.33206/mjss.541847
|View full text |Cite
|
Sign up to set email alerts
|

Yüzücülerde Stabil ve Stabil Olmayan Zeminde Yapılan Kalistenik Egzersizlerin Vücut Yağ Oranına ve Performansa Etkisi

Abstract: The aim of this study was to investigate the effect of calisthenics exercise on body fat percentage and sportive performance in swimmers. 30 swimmers between 12 and 14 years of age participated in the study voluntarily. The participants were divided into 3 groups. In the first group, 10 swimmers performed calisthenics exercise on stable ground and (4-5 units) swimming training, in the second group 10 swimmers performed calisthenics exercise on unstable ground and (4-5 units) swimming training and in the third … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 34 publications
(35 reference statements)
0
3
0
Order By: Relevance
“…Sarıkaya (2022) in his study stated that there was no statistically significant difference in the back strength values of Taekwondo in (Taekwondo practitioners) after eight weeks of bosu ball exercise in the pre-test and post-test between-groups comparison of the experimental and control groups. Bayrakdar (2020) stated in his study on child swimmers that there was a statistically significant difference in the back and leg strength parameters between the stable ground group, the unstable ground group and the control group of calisthenic exercises. Cosio-Lima et al, (2023) reported an increase in back strength values as a result of 5 weeks of core training programs.…”
Section: Discussionmentioning
confidence: 97%
“…Sarıkaya (2022) in his study stated that there was no statistically significant difference in the back strength values of Taekwondo in (Taekwondo practitioners) after eight weeks of bosu ball exercise in the pre-test and post-test between-groups comparison of the experimental and control groups. Bayrakdar (2020) stated in his study on child swimmers that there was a statistically significant difference in the back and leg strength parameters between the stable ground group, the unstable ground group and the control group of calisthenic exercises. Cosio-Lima et al, (2023) reported an increase in back strength values as a result of 5 weeks of core training programs.…”
Section: Discussionmentioning
confidence: 97%
“…Weight measurements of the subjects were measured with a scale with an accuracy of ± 100 g. During the measurement, the subjects had only shorts on, their feet were naked, and their anatomical posture was recorded as kg. It was calculated by dividing the body weight (kg) of the volunteers by the square of the height (m) value (kg/m2) (Sever, 2018;Bayrakdar Et al., 2019).…”
Section: Height Body Weight and Body Mass Indexmentioning
confidence: 99%
“…This training involves little to no equipment. For swimmers, calisthenics exercise could affect body fat percentage and swimming performance [4]. Another study among male Kabaddi players showed that plyometric and calisthenics training integrated with conventional Kabaddi training would enhance explosive power, agility, trunk/lower-extremity strength, balance, and aerobic performance [5].…”
Section: Introductionmentioning
confidence: 99%